Facile and scalable preparation of nitrogen, phosphorus codoped nanoporous carbon as oxygen reduction reaction electrocatalyst - Wang, Wei; Li, Jinmei; Kang, Yumao; Wang, Fengxia; Song, Junnan; Lei, Ziqiang (Electrochimica acta, 2017)
[Display omitted] •A facile scalable strategy to achieve N, P co-doped porous carbon.•NP-PC-0.5 exhibits good stability and resistance to methanol crossover.•NP-PC-0.5 nearly achieves 4e− pathway and produces low H2O2 yield. Herein, a series of non-precious metal catalysts, nitrogen, phosphorus co-doped porous carbon (NP-PC) materials are successfully fabricated via a facile pyrolysis and activation strategy employing low-cost precursors. Among all prepared catalysts, the optimized NP-PC-0.5 (with 0.5wt% FeCl3) possesses comparable catalytic activity to that of state-of-the-art commercial Pt/C (C-Pt/C) catalyst. Noticeably, it exhibits significantly superior methanol crossover resistance and better stability than C-Pt/C. The synergetic effect between nitrogen and phosphorus, together with nanoporous structure endow NP-PC-0.5 with practical significance of applicability, rendering it as a promising candidate of Pt-based electrocatalysts in fuel cells. This preparation approach is facile and scalable for fabricating non-precious metal electrocatalysts.